Prevalence of Geographic Tongue Disorders in Pregnant Women at Gianyar I Public Health Center Period June – July 2023 - I Gusti Ngurah Putra Dermawan; Ni Nyoman Gemini Sari; Ni Putu Andini Dewi Febriyanti (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Geographic tongue is an annular lesion that can be found on the dorsum and the edges of the tongue. This lesion is also known as erythema migrans. The clinical appearance of Geographic tongue consists of white, yellow, or gray lesions on the slightly elevated edges. This study aimed to determine the prevalence of geographic tongue cases in pregnant women at the Community Health Center Gianyar I. Material and Method: The type of research used in this study was a descriptive epidemiological research method. The total number of samples in this study was 125 respondents of pregnant women at the Community Health Center Gianyar I. Data analysis was carried out descriptively, namely those presented in the form of frequency and percentage distribution tables. Results and Discussions: From the research results, the prevalence of geographic tongue in pregnant women at the Gianyar I Community Health Center period June - July 2023, there were 11 (8.8%) sufferers of geographic tongue disorder, where based on gestational age (trimester), there were 6 sufferers of geographic tongue or around ( 11.11%) in the third trimester, while in the second trimester there were 4 (9.52%) people who suffered from geographic tongue and only 1 person (3.44%) who suffered from geographic tongue in the first trimester. Conclusion: The prevalence of geographic tongue cases is mostly found in the third trimester of pregnancy; most have no symptoms or pain.